Relationship between birth order and birth weight of the pig - Charneca, Rui (2013)
The objective of this study was to determine whether birth weight of the pig is related to its birth order. The study involved 292 sows from 2 genotypes (Large White x Landrace crossbred (LL), n= 247 and Alentejano (AL), n=45) of mixed parity and their piglets. Most sows farrowed naturally. Each piglet was identified, weighed (± 1g) (mummies excepted) and its birth order (BO) recorded within 2 min of birth. A total of 3418 LL and 375 AL piglets were born of which 43 and 7 were mummified, and 205 and 6 were stillborn, respectively. Number of total born (TB) and born alive piglets (BA) per litter ranged from 6 to 23 (mean, 13.85 ± 0.19 (se)) and from 6 to 22 (mean, 12.84 ± 0.17), and from 4 to 13 (mean, 8.33 ± 0.31) and from 4 to 12 (mean, 8.04 ± 0.31) in LL and AL litters, respectively. Within-litter regression was used to determine the relationship between BO and birth weight (PASW Statistics, version 18.0, 2009). To compare litters of different sizes, BO was expressed as relative BO (RBO) calculated as RBO = (BO-1) / (TB-1). The slopes of the regression lines relating birth weight of TB or BA piglets to RBO were positive and similar in both genotypes (P>0.50). The common slopes of the regression line relating birth weight of TB and BA piglets to RBO were: bTB = 70 ± 14 (g) RBO (P<0.0001, R2= 0.007) and bBA = 81 ± 14 (g) RBO (P<0.0001; R2= 0.009), respectively. Results indicated that birth weight of BA piglets increases by 0.81g per one percent increase in RBO. It was concluded that RBO explained a small percentage of the total variability found in piglet birth weight.